PERBANDINGAN INDEKS PELAPORAN SOSIAL KEISLAMAN ANTAR BANK-BANK UMUM SYARIAH DI INDONESIA - Erdhina Putri Riyanti; Endang Kiswara (Diponegoro Journal of Accounting, 2014)
This study aims to determine how the comparison of Islamic social reporting index/index PSKI (islamic social reporting/ISR) between Islamic banks in Indonesia. This study refers to PSKI index developed by Othman, Ghani, and Thani (2009) which has 6 theme, it is investment and financial disclosure, products and services, labor, social, environmental, and corporate governance. In addition to the six themes, this research also developed using the items on the research of Hardiyanti (2012) and Fauziah and Yudho (2013) as well as adding one new theme is a theme islamic.This research was conducted using qualitative comparative descriptive with descriptive statistics. This research is a comparative study of the object by using descriptive statistical explanation. The comparison includes items related to the contribution of ownership and Sharia Supervisory Board.The results showed that the Bank Syariah Mandiri has the highest score on the index investing and financing PSKI themes, products and services, labor, and social. Bank Muamalat, BRI Syariah, and BJB Sharia obtain the same score on the theme of environment, 1 score. PSKI theme On the index of corporate governance, Bank Syariah Mandiri Bank Syariah Bukopin, and Bank Mega Syariah obtain the highest score of 7. Overall highest score owned by Bank Muamalat, which is 40. Bank Syariah Mandiri is superior in several themes but because ISR index score on islamic theme is negative so the score ended up being lower than the Bank Muamalat. These results imply that the performance index of social reporting has close relation with Islamic patterns are also entitled Islamic finance.